Pengaruh Perencanaan Fasilitas Dan Koordinasi Terhadap Kualitas Pelayanan Persampahan; Studi Di Kota Bandung, Kabupaten Bandung, Kabupaten Sumedang dan Kota Cimahi - Bustami, Thomas (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2012)
The main problem discussed in this research is low quality of solid waste services in Bandung Municipality, Bandung Regency, Surnedang Regency and Cimahi Municipality. This research is designed as an explanatory survey, with qualitative and quantitative approach. The quantitative data was analysed using PATH Analysis. The result demonstrates that facilities planning both partially and simultaneously affected the solid waste services quality. Likewise, the coordination either directly or indirectly affected the solid waste services quality. it was obvious that the solid waste services quality was significantly affected by the two variables.